2021
DOI: 10.1038/s41467-021-22509-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-world stress resilience is associated with the responsivity of the locus coeruleus

Abstract: Individuals may show different responses to stressful events. Here, we investigate the neurobiological basis of stress resilience, by showing that neural responsitivity of the noradrenergic locus coeruleus (LC-NE) and associated pupil responses are related to the subsequent change in measures of anxiety and depression in response to prolonged real-life stress. We acquired fMRI and pupillometry data during an emotional-conflict task in medical residents before they underwent stressful emergency-room internships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 147 publications
6
45
0
Order By: Relevance
“…Moreover, a vast number of studies have shown that a network of cortical and subcortical regions (including the ventral striatum and the anterior cingulate cortex) are involved in increasing attention and cognitive control in various tasks to maximize reward outcomes [5,73]. More recently, the locus coeruleus-norepinephrine system has been linked to the allocation of cognitive control [74,75]. In the context of the present study, it might be interesting to investigate how far activity modulations in these regions would vary with the degree of contingency between the performed action and the outcome (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a vast number of studies have shown that a network of cortical and subcortical regions (including the ventral striatum and the anterior cingulate cortex) are involved in increasing attention and cognitive control in various tasks to maximize reward outcomes [5,73]. More recently, the locus coeruleus-norepinephrine system has been linked to the allocation of cognitive control [74,75]. In the context of the present study, it might be interesting to investigate how far activity modulations in these regions would vary with the degree of contingency between the performed action and the outcome (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Pupillary diameter, corneal multifocality, and aberration may contribute to accommodation [ 31 34 ], with pupillary diameter most likely in 2020–21 [ 31 ]. A recent investigation using fMRI and pupillometry in medical residents found neural responsitivity of the noradrenergic locus coeruleus and associated pupil responses are related to changes in anxiety and depression in response to prolonged real-life stress [ 35 ]. Longitudinal survey results identified a worsening of psychological distress with COVID-19-related stressors [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Again, we can only speculate the mechanisms of action of this training program. In a previous study on frontline medical workers, we found that lower activation of the arousal system, indexed by activation of the arousal system during an emotion regulation task, was associated with increased resilience during subsequent stressful medical work [ 55 ]. Since one demonstrated effect of mindfulness is a change in gray matter concentration in several brain regions, including the locus coeruleus arousal system [ 56 ], such changes may well underlie the effects of mindfulness interventions and could be important to the first responder populations.…”
Section: Discussionmentioning
confidence: 99%